BUILDING SOCIAL AND ECOLOGICAL AWARENESS OF STUDENTS OF SMP NEGERI 4 TENGGARONG THROUGH PPKN LEARNING IN THE CONTEXT OF THE IMPACT OF COAL MINING IN TENGGARONG - M. Damarjati Anis Lutfi; Suryaningsi Suryaningsi; Alim Salamah; Novita Majid (SOSIOEDUKASI, 2025)
This study aims to determine the strategies and roles of teachers in increasing students' awareness and responsiveness to the socio-ecological impacts of coal mining activities at at Tenggarong Junior High School, East Kalimantan. The study used a descriptive qualitative approach with research subjects consisting of the vice principal, social studies and civics teachers, and students. Data were collected through observation, interviews, and documentation, then analyzed through the process of reduction, presentation, and drawing conclusions. The results of the study showed that students' awareness was still relatively low due to the lack of environmental education in the curriculum and the lack of information from external sources. The strategies implemented by teachers in learning such as the use of local case studies, focus group discussions, collaborative projects, and the Problem-Based Learning (PBL) approach were proven to be effective in increasing students' awareness and responsiveness. The improvement was seen from the results of the pre-test and post-test as well as the quality of project work such as mind mapping. This study emphasizes the importance of integrating socio-ecological education in the learning process to form a generation that is critical, environmentally conscious, and socially responsible.